2014
DOI: 10.3109/09537104.2014.988694
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multiplate platelet aggregometry using citrate, heparin or hirudin in Rhesus macaques

Abstract: Electrical impedance aggregometry (EIA) has gained popularity for clinical and research applications. Nonhuman primates are used to study disease and drug-related mechanisms that affect hemostasis, therefore normal establishing normal EIA parameters are necessary. The anticoagulants sodium heparin, hirudin and sodium citrate and three agonists, ADP, ASPI, and collagen were evaluated. Whole blood from 12 adult male rhesus macaques was collected to evaluate anticoagulants, sodium heparin, hirudin and sodium citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, some differences in aggregation between hirudinated and heparinated PRP could not be explained so readily. It has been reported that heparin is capable of inducing the micro-aggregate formation in PRP, which are potentiating further platelet aggregation as well as false-positive LTA results 39 . Furthermore, it has been demonstrated that heparin is a positive mediator of platelet integrin function 40 and thus, in heparinized PRP platelet aggregation might be additionally potentiated.…”
Section: Discussionmentioning
confidence: 99%
“…However, some differences in aggregation between hirudinated and heparinated PRP could not be explained so readily. It has been reported that heparin is capable of inducing the micro-aggregate formation in PRP, which are potentiating further platelet aggregation as well as false-positive LTA results 39 . Furthermore, it has been demonstrated that heparin is a positive mediator of platelet integrin function 40 and thus, in heparinized PRP platelet aggregation might be additionally potentiated.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical applications of platelet reactivity testing has put a focus on development of novel strategies for platelet reactivity assessment [ 14 ]. But with the development of new and improved hemostatic assessment methods, the issue of the correct pre-analytical conditions, such as which anticoagulant and concentration to use, has been receiving increased attention from researchers [ 7 10 , 15 ]. Thus, the aim of our study was to clarify some of the issues regarding anticoagulant use in LTA.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that both ADP and collagen caused weaker platelet impedance responses in citrated whole blood samples compared to hirudinized samples [ 8 ]. The inferiority of sodium citrate as an anticoagulant in impedance whole-blood aggregometry has thus been well documented [ 7 10 ]. Nevertheless, conclusive evidence with an extensive range of the Clinical and Laboratory Standards Institute (CLSI) Platelet Function Testing by Aggregometry Approved Guideline recommended agonists [ 11 ], using both sodium citrate and hirudin as anticoagulants in LTA, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have shown that platelet aggregation in heparin anti-coagulated blood is higher than in sodium citrate anti-coagulated blood using different blood samples. 12,13 In sodium citrate anti-coagulated blood, Ca 2+ in the blood, which is necessary for platelet activation and aggregation, chelates with sodium citrate. However, Ca 2+ levels do not decrease in heparin anti-coagulated blood, as calcium chelation does not occur.…”
Section: Discussionmentioning
confidence: 99%